An empirical analysis of cultural ecosystem values in coastal landscapes. (15th June 2017) - Brown, Greg; Hausner, Vera Helene
Abstract: Coastal areas are especially important to human well-being with half the world's population living within 60 km of the sea and three-quarters of all large cities located in the coastal zone. Supporting and regulatory ecosystem services in coastal areas have received considerable research attention given human vulnerability to climate change, but cultural ecosystem services in the coastal zone are less understood. This study describes and analyzes the distribution of cultural ecosystem values found in coastal areas in multiple countries (n = 5) and compares the results with non-coastal areas. Mapped cultural ecosystem values were collected from public participation GIS (PPGIS) processes in the U.S., Australia, New Zealand, Norway, and Malaysia and analyzed to identify the type and intensity of ecosystem values located in coastal areas. Mapped ecosystem values were significantly more abundant in all coastal zones, regardless of ecosystem value category, country, population, or dominant land use. Compared to cultural ecosystem values, biological and life-sustaining values were mapped less frequently in the coastal zone. Economic and social values were significantly associated with developed (built) coastal zones, while aesthetic and recreation values were more strongly associated with natural coastal zones. Coastal access, especially by road, influences the mix of perceived values from nature-based values to anthropocentric values. Coastal zones will continue to be the principle location for potential future land use conflict given their high social and cultural value relative to other ecological values. Understanding trade-offs in coastal zone planning and management requires a systematic inventory of the full range of ecosystem services, including cultural services. Highlights: Examines distribution of cultural ecosystem values in coastal areas in five countries. Mapped values more abundant in all coastal zones regardless of ecosystem value. Economic and social values were significantly associated with developed (built) coastal zones. Biological and life-sustaining values were mapped less frequently than cultural values. Coastal zones will continue to have land use conflict given high cultural and ecological value.